"Return of the repressed": Exposure to police violence increases protest and self-sacrifice intentions for the Yellow Vests. (December 2020) - Adam-Troian, Jais; Çelebi, Elif; Mahfud, Yara
Worldwide, it is not uncommon to observe violent police reactions against social movements. These are often rationalized by decision makers as efficient ways to contain violence from protesters. In France for instance, the ongoing Yellow Vests protests have generated an unprecedented number of casualties, injuries, and convictions among protesters. But was this response efficient in diminishing violence stemming from the Yellow Vests? To this day, little is known about the psychological consequences of police violence in the context of protests. Combining insights from Significance Quest Theory and the Social Identity perspective on collective action, we predicted that exposure to police violence could "backfire" and lead to increased radicalization of protesters. A cross-sectional investigation of 523 Yellow Vests yielded evidence for this hypothesis. We found positive direct effects of exposure to police violence on intentions to attend future demonstrations and to self-sacrifice for the Yellow Vests. Moreover, these effects were serially mediated by perceived Loss of Significance and Identification with the Yellow Vests. Paradoxically, these results highlight for the first time the mechanism through which political repression may contribute to the formation of radical politicized identities. Thus, we recommend that decision makers privilege the use of de-escalation techniques in protest policing whenever possible.